Toxicity evaluation of laser-synthesized pro-angiogenic carbon monoxide-rich gold nanoparticles in vitro and in vivo - Gomes Araujo, Thais Braga; Concas, Guilherme Conceição; Gisbert, Mariana; Araujo, Gabriel de Farias; Boldrini Pereira, Leonardo da Cunha; Corrêa Maduro, Lorena Gonçalves Henriques; Soares, Lorena Oliveira Souza; Sales Junior, Sidney Fernandes; Cunha, Davi Pinheiro; Correia, Fábio Veríssimo; Laurenzana, Anna; Anceschi, Cecilia; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe safety profile of gold nanoparticles remains a concern and depends on dose, size, surface chemistry and charge. This study evaluated through in vitro and in vivo methods the cytotoxicity, oxidative stress and genotoxicity of laser synthesized carbon monoxide-Rich Gold Nanoparticles (COR-AuNPs), which can strongly promote angiogenesis in endothelial colony forming cells (ECFC).MethodsCOR-AuNPs were synthesized by pulsed laser driven CO2 reduction reaction, and stabilized for culture media with the addition of the copolymer Pluronic-F127 (PF127). The fresh synthetized nanoparticles where characterized for size and morphology. Their stability was investigated in both culture media and the water aquarium environment. In vitro Cytotoxicity was assessed using the MTS assay on SaOS-2 cells and trypan blue staining in ECFCs at concentrations of 5 and 10 × 103 μg.L−1. Zebrafish were exposed to a maximum concentration of 75 μg.L−1 of COR-AuNPs for 96 h. Oxidative stress biomarkers were assessed in liver and brain tissues, while genotoxicity was evaluated using the comet assay. The analyzed biomarkers included superoxide dismutase, catalase, reduced glutathione, total antioxidant capacity, carbonylated protein, and malondialdehyde.ResultsThe PF127 stabilized COR-AuNPs are stable in the zebrafish aquarium water for 6 weeks and showed no precipitation in the culture media. A strong pro-angiogenic activity was observed for ECFCs exposed to the COR-AuNPs at a minimal concentration of 5 × 103 μg.L−1. The CO release is not immediate in the culture medium, suggesting that the COR-AuNPs are characterized by an intracellular release. No significant cytotoxicity was observed in both ECFC or SaOS-2 cells, and most oxidative stress biomarkers showed no significant effects in zebrafish. However, reduced glutathione levels decreased significantly in the brain at concentrations between 10 and 35 μg.L−1, likely due to the interaction with the metallic surface of the nanoparticles, while in the liver they increased significantly following exposure to COR-AuNPs at concentrations between 20 and 75 μg.L−1. No genotoxic effects were detected in zebrafish.ConclusionCOR-AuNPs enhance capillary morphogenesis in ECFCs, with minimal cytotoxicity, oxidative stress, and genotoxicity at sublethal concentration, supporting their safety for potential applications in regenerative therapies.